Didactics of the Fundamentals of Computer Programming with a Computational Thinking Approach Based on Turtle Graphs - Jesus Insuasti; Edwin Insuasty; Alexander Baron (Academia y Virtualidad)
Computer programming fundamentals often present significant challenges, particularly in developing computational thinking and problem solving skills. In Colombia, several higher education institutions have reported high dropout rates in introductory programming courses, according to government data. In response to this issue, a qualitative study with quantitative components is proposed, adopting a case study approach aimed at enhancing the teaching of the “Computer Programming Fundamentals” course at the University of Nariño, in Pasto, southern Colombia. The research introduces the use of Turtle computational graphics through Flowgorithm, a tool originally proposed by Sacramento State University in California. Widely used in the 1980s, Turtle graphics provide a unique and engaging method for teaching computational thinking through programming. By translating code into visual movements and drawings, this approach helps bridge the gap between abstract programming concepts and tangible understanding—particularly beneficial for beginners. Flowgorithm’s implementation of Turtle graphics introduces essential programming concepts in a fun and interactive environment. This method fosters greater confidence in novice programmers and nurtures deeper interest in the subject, thereby significantly improving learning outcomes. In a study involving sixty-six students enrolled in the course, the approach yielded promising results. Students were able to immediately observe the effects of their code, promoting experimentation, creativity, and visual evaluation of their algorithms—key factors in developing strong problem-solving skills.